2023
DOI: 10.51847/gdcamtoqll
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Staging and Clinicopathologic Features Presenting to Oral & Maxillofacial Surgery Practice in Saudi Arabia

Abstract: The most common type of head and neck cancer, oral cancer (OC), is the 16th most common malignancy and the 15th most frequent cause of cancer-related deaths in the world. There has been an increase in the incidence of OC in Saudi Arabia in recent years. The survival rate of oral cancer is one of the lowest in the world and still, unfortunately, a large number of OC cases are discovered in advanced stages. The purpose of this study is to assess the prevalence of advanced stages of oral cancer in maxillofacial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Today, cosmetic surgery is considered one of the most common surgeries in the world, and its use is increasing. Cosmetic surgery is a reconstructive surgery that was initially used to remove congenital lesions, but in the later stages, it was used for cosmetic purposes [1][2][3][4]. With the increasing demand for cosmetic surgery, numerous studies conducted in this field have identified factors such as dissatisfaction with body image, low attractiveness, body deformity disorder, social and interpersonal factors, cultural factors, the influence of media advertising and fashion as influencing variables on have introduced this trend [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Today, cosmetic surgery is considered one of the most common surgeries in the world, and its use is increasing. Cosmetic surgery is a reconstructive surgery that was initially used to remove congenital lesions, but in the later stages, it was used for cosmetic purposes [1][2][3][4]. With the increasing demand for cosmetic surgery, numerous studies conducted in this field have identified factors such as dissatisfaction with body image, low attractiveness, body deformity disorder, social and interpersonal factors, cultural factors, the influence of media advertising and fashion as influencing variables on have introduced this trend [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%